THE STATE OF THE ART IN ACROBATIC GYMNASTICS: A BIBLIOMETRIC ANALYSIS - Isaura Leite; Pedro Fonseca; Lurdes Ávila-Carvalho; João Paulo Vilas-Boas; Márcio Goethel; Luis Mochizuki; Filipe Conceição (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
Since acrobatic gymnastics is a recent gymnastics discipline, with only a few decades old, with only a few decades old, it is not yet much explored as a scientific research field. Despite its increasing popularity, and while science mapping has become an essential activity for all scientific disciplines, no bibliometric analysis on this topic was available. Therefore, this study aims to provide a static picture of the scientific research development in acrobatic gymnastics by collecting information about the main contributors as well as the main investigation topics, the publication dynamics and cooperative networks. A search conducted in the Web of Science and Scopus databases retrieved 37 journal articles between 2001-2021. Results suggest that the year of 2015 was a milestone for scientific research in acrobatic gymnastics since it marked the beginning of the dominance of authors from Spain, followed by Poland and Portugal. Countries are generally focused on their own territory and there is a limited scientific collaboration between different nations. The Spanish and the Polish research institutions are leading publishing in this sport. As a reference for future studies, our results suggest that although balance was identified as the niche investigation topic, there has been a lack of interest for the pyramids balance, which is a major feature of acrobatic gymnastics.